In silico analysis of four structural proteins of aphthovirus serotypes revealed significant B and T cell epitopes. (March 2019) - Raza, Sohail; Siddique, Kalsoom; Rabbani, Masood; Yaqub, Tahir; Anjum, Aftab Ahmad; Ibrahim, Muhammad; Azhar, Muhammad; Jamil, Farrukh; Rasheed, Muhammad Asif
Abstract: Foot and Mouth disease (FMD) is economically devastating, highly contagious transboundry viral disease of livestock with 100% morbidity, rapid spread and severe production losses in animals. The FMDV has seven different serotypes. There is no vaccine that can protect animals from all serotypes. Hence, it is need of the day to develop a vaccine that protects animals from hetrologous challenge. In this study, we used immunoinformatics approach to find T and B-cell epitopes that will help to construct a universal vaccine for FMDV. For this purpose, first we constructed a consensus sequence for four structural proteins (VP1, VP2, VP3 and VP4) of aphthovirus for seven serotypes (A, O, C, Asia1, SAT1, SAT2 and SAT3). Various computational tools were used to perform multiple sequence alignment to identify the conserved regions, generation of consensus sequence through conserved regions, structures prediction and finally prediction of B and T cell epitopes. We predicted 5 B cell and 18 T cell epitopes. Finally a GPGPG spacer was used to join these epitopes to decrease binding affinity around the core binding regions. Hence, our study identified the epitopes which can be used to develop cross protective vaccines against all the fatal strains of Aphthovirus which can easily protect all the serotypes. Though, successful In vivo and In vitro studies are required to determine the genuine strength of our predicted epitopes against the fatal strains of Aphthovirus.